2018
DOI: 10.1016/s2213-8587(18)30050-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes duration and glycaemic control on 14-year cause-specific mortality in Mexican adults: a blood-based prospective cohort study

Abstract: SummaryBackgroundDiabetes is a cause of at least a third of all deaths in Mexican adults aged 35–74 years, with the excess mortality due mainly to vascular disease, renal disease, infection, and acute diabetic crises. We aimed to analyse the effect of diabetes duration and glycaemic control on death rate ratios (RRs) for these causes and to assess the relevance to cause-specific mortality of undiagnosed diabetes.MethodsAbout 100 000 women and 50 000 men aged 35 years or older from Mexico City were recruited in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 20 publications
6
67
1
Order By: Relevance
“…In the current study, the rate of mortality increased with diabetes duration. Our finding is consistent with previous studies [19][20][21] ; In the Verona Diabetes Study (VDS), death rates rose in both sexes with increasing duration of diabetes 19 . In a cohort study, a10-yearlonger duration of diabetes was correlated with a 1.2-1.3 times increased risk of all-cause mortality in Australian patients with diabetes 20 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, the rate of mortality increased with diabetes duration. Our finding is consistent with previous studies [19][20][21] ; In the Verona Diabetes Study (VDS), death rates rose in both sexes with increasing duration of diabetes 19 . In a cohort study, a10-yearlonger duration of diabetes was correlated with a 1.2-1.3 times increased risk of all-cause mortality in Australian patients with diabetes 20 .…”
Section: Discussionsupporting
confidence: 93%
“…In a cohort study, a10-yearlonger duration of diabetes was correlated with a 1.2-1.3 times increased risk of all-cause mortality in Australian patients with diabetes 20 . Another study in Mexico reported significantly increased rates of death from diabetes with duration of diabetes 21 . Longer duration of diabetes (equivalent to diagnosis of diabetes at younger age) increases the exposure to hyperglycaemia, which is correlated to an increased risk of complications 16,17,22 .…”
Section: Discussionmentioning
confidence: 97%
“…The management of long‐standing type 2 diabetes remains an important challenge. In addition to the difficulties of maintaining glycaemic control, long duration of diabetes is associated with an increase in cardiovascular complications and progressive renal decline, which in turn contribute to heightened rates of morbidity and mortality in these patients . While much is known about the association of diabetes duration with rates of complications, considerably less is known about the details of the efficacy and safety of antihyperglycaemic agents, such as GLP‐1 analogues, as diabetes duration increases, particularly if GLP‐1 analogues have consistent cardiorenal efficacy across different durations of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of type 2 diabetes is an important determinant of cardiovascular and renal outcomes . However, less is known about whether antihyperglycaemic agents exert a consistent benefit on these outcomes as duration of type 2 diabetes increases.…”
Section: Introductionmentioning
confidence: 99%
“…A recent, similar study from Mexico assessed the effect of diabetes on cause-specific mortality [12]. In low- and middle-income countries the prevalence and complications resulting from diabetes are expected to increase, but in Mexico there is already a 4-fold increase in the mortality risk with a diabetes diagnosis.…”
Section: Diabetic Nephropathy: Hiddo Lambers Heerspink (The Netherlands)mentioning
confidence: 99%